Silencing of Neuroligin Function by Postsynaptic Neurexins - Taniguchi, Hiroki (Society for Neuroscience, 2007)
The formation of neuronal circuits during development involves a combination of synapse stabilization and elimination events. Synaptic adhesion molecules are thought to play an important role in synaptogenesis, and several trans-synaptic adhesion systems that promote the formation and maturation of synapses have been identified. The neuroligin–neurexin complex is a heterophilic adhesion system that promotes assembly and maturation of synapses through bidirectional signaling. In this protein complex, postsynaptic neuroligins are thought to interact trans-synaptically with presynaptic neurexins. However, the subcellular localization of neurexins has not been determined. Using immunoelectron microscopy, we found that endogenous neurexins and epitope-tagged neurexin-1β are localized to axons and presynaptic terminals in vivo. Unexpectedly, neurexins are also abundant in the postsynaptic density. cis-expression of neurexin-1β with neuroligin-1 inhibits trans-binding to recombinant neurexins, blocks the synaptogenic activity of neuroligin-1, and reduces the density of presynaptic terminals in cultured hippocampal neurons. Our results demonstrate that the function of neurexin proteins is more diverse than previously anticipated and suggest that postsynaptic cis-interactions might provide a novel mechanism for silencing the activity of a synaptic adhesion complex.